A new paradigm for city life; bringing Borlänge´s center back to the human scale - Lindman, Linnéa (My University, 2025)
The thesis has addressed urban planning from an era focused on modernizing cities and promoting the independent, free human being, an identity closely tied to the car. This approach has deteriorated pedestrian life and removed essential urban functions. Consequently, car-centric cities that have left little room for alternative mobility, urban life, detail, or interaction on the city’s fundamental infrastructure: The Street. This thesis has aimed to define principles of sustainable, healthy, and democratic urban areas where people want to engage. The objective has been to develop a proposal strengthening pedestrian city life in Borlänge’s core, with emphasis on revitalizing Borgarnäsvägen, an important connection with historical value. The proposal was grounded in urban principles, functions, and aesthetics that reflect local identity, promote inclusivity, and encourage community and movement. The thesis has addressed three main questions: 1) ”What key elements should a city incorporate from a sustainability perspective?”, 2) ”How might the urban landscape and human behavior evolve if the car-centric norm were challenged?”, and 3) “Which cultural and local aspects should be emphasized in Borlänge?” The background outlined the car-centric city’s evolution, focusing on Borlänge’s centers transformation in the 1960s. It also reviewed a 1994 article envisioning “Borlänge år 2024” and its reflections on the city’s character, including the historically significant Borgarnäsvägen. The theoretical part has established key principles for developing human-scale cities and has presented methods for shaping urban spaces. The methods included literature reviews, a site analysis, photo studies, site visits, and inventories. The expected results include an urban analysis of the challenges and opportunities in central Borlänge. This has informed a vision for the center, focusing on a human-scale urban environment that fosters social activities and urban life. Additionally, a design suggestion was presented, aimed at activating the trafficked section of Borgarnäsvägen, grounded in local aesthetics, the site, culture, functionality, and materiality to promote movement, activity, and social interaction. This is presented to encourage further discussion and imagination about how Borgarnäsvägen could be transformed.
Keywords: Urban planning; Human scale; Human pace; Edge zones; Pedestrian